Spontaneous grafting of nitrobenzenediazonium salt on plasma-modified copper substrates - Su, Jiangling; Muhle, Marius; Nembot, Nelly; Prüßner, Tim; Xie, Xiaofan; Wittstock, Gunther; Grundmeier, Guido (Electrochimica Acta)

Digitale Kompetenzen für Lehrkräfte in der beruflichen Bildung – Beiträge zur Modellierung, Messung und Förderung - Sänger, Niklas
Die digitale Transformation stellt Lehrkräfte vor eine doppelte Herausforderung: Sie sind selbst Lernende im Zuge des Wandels und gleichzeitig dafür verantwortlich, digitale Kompetenzen bei ihren Lernenden zu fördern. Aus Sicht der beruflichen Bildung besteht eine weitere Herausforderung darin, dass Lehrkräfte zwischen zwei inhaltlichen Referenzsystemen – wissenschaftsorientiertem Fachwissen und praxisbezogenem beruflichem Wissen – vermitteln müssen. Bisherige Forschungsarbeiten fokussieren jedoch primär medienpädagogische Aspekte und vernachlässigen den Einfluss der digitalen Transformation auf die fachlichen Lerngegenstände sowie damit verbundene fachdidaktische Implikationen. Die Dissertation adressiert diese Forschungslücke, indem sie untersucht, wie digitale Kompetenzen von Lehrkräften in der beruflichen Bildung konzeptualisiert, empirisch erfasst und curricular integriert werden können. Sie verfolgt dabei drei zentrale Fragestellungen: (1) Wie lassen sich digitale Kompetenzen im Kontext des doppelten Gegenstandsbezugs theoretisch fundieren? (2) Wie kann ein entsprechendes Kompetenzmodell empirisch operationalisiert werden? (3) Welche Implikationen ergeben sich daraus für die curriculare Gestaltung von Lehramtsstudiengängen? Im Rahmen der kumulativen Dissertation wird zunächst das TPACK-Modell kritisch analysiert und für den Kontext der beruflichen Bildung erweitert. Darauf aufbauend wird ein Messinstrument zur Erfassung digitaler Kompetenzen entwickelt und empirisch validiert. Zudem wird ein hochschuldidaktisches Konzept zur curricularen Integration digitaler Kompetenzen entwickelt und reflektiert. Die Ergebnisse zeigen, dass der doppelte Gegenstandsbezug ein zentrales Strukturmerkmal digitaler Kompetenzen in der beruflichen Bildung darstellt und bei der Ausbildung von Lehrkräften systematisch berücksichtigt werden muss. Die Dissertation leistet einen konzeptionellen und empirischen Beitrag für den Diskurs um digitale Kompetenzen in der beruflichen Bildung und gibt konkrete Impulse für die Professionalisierung von Lehrkräften im Zuge der digitalen Transformation.

Didaktische Überlegungen in der Psychologie - Scharlau, Ingrid; Jenert, Tobias (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Studiengangentwicklung - Jenert, Tobias (Hochschulforschung)
This handbook systematises the current state of knowledge on subjects of higher education research. It examines research, teaching and studies, the transfer of knowledge related to research and teaching as well as universities as organisations and their functions in the education and training systems. By looking at the topics over time, this standard work also provides information on university developments and their current state. The following question is answered in 60 articles: What do we currently know about the topic under discussion, what is the current state of research and what has remained unanswered so far? This book is aimed at higher education, academic and educational research as well as practitioners in higher education development and higher education policy.With contributions byNicole Auferkorte-Michaelis | Julia Backhaus | Ulf Banscherus | Annette Barkhaus | Lukas Baschung | Lorenz Blume | Stefan Böschen | Carla Bohndick | Gesche Brandt | Kolja Briedis | Rainer Bromme | Till Bruckermann | Juri Dachtera | Jennifer Dusdal | Melinda Erdmann | Gregor Fabian | Marian Füssel | Max-Emanuel Geis | Nicolai Götze | Gabriele Gramelsberger | Insa Großkraumbach | Julian Hamann | Christophe Heger | Thomas Heinze | Justus Henke | Sandra Hofhues | Arlette Jappe | Tobias Jenert | Stefan John | Wolfgang Jütte | Marco Kalz | Michael Kerres | Bernd Kleimann | Robert Kordts | Anna Kosmützky | Georg Krücken | Ines Langemeyer | Michelle Latta | Inge Leurs | Avelina Lovis-Schmidt | Sylvi Mauermeister | Marianne Merkt | Björn Möller | Richard Münch | Martin Neugebauer | Axel Oberschelp | Peer Pasternack | Attila Pausits | Axel Philipps | Manuel Pietzonka | Philipp Pohlenz | Justin J. W. Powell | Carole Probst | Martin Reinhart | Gabi Reinmann | Rüdiger Rhein | Heiner Rindermann | Heinke Röbken | Ronny Röwert | Gudrun Rohde | Niclas Schaper | Mandy Schiefner-Rohs | Christian Schneijderberg | Elmar Schüll | Marcel Schütz | Dagmar Simon | Isabel Steinhardt | Jana Stibbe | Friedrich Stratmann | Niels Taubert | Ulrich Teichler | Ewald Terhart | Peter Tremp | Martin Unger | Susanne de Vogel | Klaus Wannemacher | Christian Wassmer | Inka Wertz | Oliver Wieczorek | Johanna Witte | Andrä Wolter | Grit Würmseer

Fostering self-regulated entrepreneurial learning in entrepreneurship education - Fahrbach, Manuel; Jenert, Tobias; Fust, Alexander; Bellwald, Noah; Winkler, Christoph (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Self-Regulated Learning; Entrepreneurship Education; Entrepreneurship Research

Transferability as a key to impactful entrepreneurship education outcomes: a new quest - Winkler, Christoph; Jenert, Tobias; Fust, Alexander (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Methodology; Entrepreneurship Education; Entrepreneurship Research

Innovation und Transfer in der kommunalen Bildungsarbeit. Erfahrungen aus zehn Jahren wissenschaftlicher Begleitung der Transferinitiative Kommunales Bildungsmanagement - Euler, Dieter; Sloane, Peter F. E.; Jenert, Tobias; Daniel-Söltenfuß, Desiree; Hagemeier, Daniel; Ludolph, Fabian; Fuhrmann, Joelle

The Multifaceted Nature of Self-Regulation in Entrepreneurship: A Latent Class Analysis - Jenert, Tobias; Büker, Ronja (21th Biennial EARLI Conference)

Innovieren, Transferieren, Gestalten: Eine Wissenschaft, die sich verständigt - Jenert, Tobias (bwp@profil)

Der Logarithmus zur Bestimmung des pH-Wert-Verlaufs einer Titration: Ein fächerverbindender Unterrichtsvorschlag unter Verwendung digitaler Werkzeuge - Bender, Roland; Witte, Thomas; Hattermann, Matthias; Fechner, Sabine (Neue Materialien für einen realitätsbezogenen Mathematikunterricht)

Sustainable educational innovation in Higher Education: Upscaling, transfer, and student involvement - Jenert, Tobias

An Empirical Study of Large Language Models for Type and Call Graph Analysis in Python and JavaScript - Shivarpatna Venkatesh, Ashwin Prasad; Sunil, Rose; Sabu, Samkutty; Mir, Amir M.; Reis, Sofia; Bodden, Eric (Empirical Software Engineering)
Large Language Models (LLMs) are increasingly being explored for their potential in software engineering, particularly in static analysis tasks. In this study, we investigate the potential of current LLMs to enhance call-graph analysis and type inference for Python and JavaScript programs. We empirically evaluated 24 LLMs, including OpenAI's GPT series and open-source models like LLaMA and Mistral, using existing and newly developed benchmarks. Specifically, we enhanced TypeEvalPy, a micro-benchmarking framework for type inference in Python, with auto-generation capabilities, expanding its scope from 860 to 77,268 type annotations for Python. Additionally, we introduced SWARM-CG and SWARM-JS, comprehensive benchmarking suites for evaluating call-graph construction tools across multiple programming languages. Our findings reveal a contrasting performance of LLMs in static analysis tasks. For call-graph generation, traditional static analysis tools such as PyCG for Python and Jelly for JavaScript consistently outperform LLMs. While advanced models like mistral-large-it-2407-123b and gpt-4o show promise, they still struggle with completeness and soundness in call-graph analysis across both languages. In contrast, LLMs demonstrate a clear advantage in type inference for Python, surpassing traditional tools like HeaderGen and hybrid approaches such as HiTyper. These results suggest that, while LLMs hold promise in type inference, their limitations in call-graph analysis highlight the need for further research. Our study provides a foundation for integrating LLMs into static analysis workflows, offering insights into their strengths and current limitations.

Einsatz digitaler Messwerterfassung in kontextualisierten Lernumgebungen im Bereich Bildung für nachhaltige Entwicklung - Ponath, Jonas; Pollmeier, Pascal; Fechner, Sabine (40. Fortbildungs- und Vortragstagung der Fachgruppe Chemieunterricht der Gesellschaft Deutscher Chemiker e.V. (GDCh))
Keywords: Digital; Digitalisierung; Messsensoren; Fortbildung; Lehrkräfte; Chemie; Nachhaltigkeit; Bildung für nachhaltige Entwicklung; BNE

Evaluation digitalisierungsbezogener Fortbildungen für Chemielehrkräfte - Pollmeier, Pascal; Bohrmann-Linde, Claudia; Cornelius, Soraya; Grandrath, Rebecca; Rubner, Isabel; Siepmann, Karin; Sommer, Katrin; Fechner, Sabine (Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik e.V. (GDCP))
Keywords: Digital; Digitalisierung; Künstliche Intelligenz; KI; Messsensoren; Fortbildung; Lehrkräfte; Chemie

Multiphoton, multimode state classification for nonlinear optical circuits - Kopylov, Denis A.; Offen, Christian; Ares, Laura; Wembe Moafo, Boris Edgar; Ober-Blöbaum, Sina; Meier, Torsten; Sharapova, Polina R.; Sperling, Jan (Physical Review Research)
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which is in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.

Multiphoton, multimode state classification for nonlinear optical circuits - Meier, Torsten; Sharapova, Polina R.; Sperling, Jan; Ober-Blöbaum, Sina; Wembe Moafo, Boris Edgar; Offen, Christian
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which being in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.

Videobasierte Lehr-Lern-Settings entwickeln: Bildung für nachhaltige Entwicklung in der Kita als interdisziplinärer Lehr- und Lerngegenstand. Workshop am Tag der Lehre zum Thema: „Teaching for Future - Nachhaltige Lehre und Lehre über Nachhaltigkeit“. Universität Paderborn. - Büker, Petra; Göddertz, Nina; Glawe, Katrin; Reichenbach, Alexandra; Wagner, Melanie

Starting early or late? Parental perspectives on the onset of English language education at primary school in Germany - Rumlich, Dominik; Porsch, Raphaela (Early language education in instructed contexts)
Abstract This study investigates parents’ perspectives on the preferred onset of English education in Germany and potential explanatory factors drawing on a cross-sectional survey of 2,645 parents from the EUBE project ( E nglisch u nterrichts b eginn aus E lternsicht / Parental perspectives on the onset of English Language Education). Results reveal that a significant majority of parents advocate for an early start in year 1 or 2 of primary school, generally aligning with their strong conviction of the importance of English, high educational aspirations and expectations, and their own (early) start of language education. The findings contribute to a deeper understanding of parental perspectives that have also shown to be related to multiple indicators of educational success in general and achievements in language learning in particular.

Das Lehr‑/Lernkonzept inklud‐e: Durch videobasierte Fallarbeit Studierende des Grundschullehramtes für Inklusion sensibilisieren - Herding, Jana; Glawe, Katrin; Caci, Stefania Vita; Büker, Petra (Diskurse und Praktiken der Heterogenität)

PrimOER: Professionalisierung der Grundschullehrkräftebildung durch eine neue „Kultur des Teilens“ in der Lehre. Posterbeitrag auf der 33. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der PH Vorarlberg, Österreich. - Büker, Petra; Kamin, Anna-Maria; Oevel, Gudrun; Bernasconi, Bernadette; Löwen, Jana; Bruhnke, Lorena; Knurr, Moritz